STILL PLAYING WITH THE PAST: HISTORY, HISTORIANS, AND DIGITAL GAMES. Issue 4 (30th November 2022) - Wright, Esther
ABSTRACT: Playing with the Past: Digital Games and the Simulation of History, edited by Matthew Wilhelm Kapell and Andrew B. R. Elliott, was a significant publication in the establishment of historical (digital) game studies, a field that has since continued to grow. This review essay notes some of the key interventions made by the edited collection and its scope in accounting for the complexities of digital historical games. It also reflects on what the book represented at the early stages of the discipline and the ways in which scholarly approaches have developed (or not) in the decade since its publication. In doing so, it focuses on several key areas that arose in Playing with the Past and have remained central to historical game studies. In particular, this essay examines questions of digital games' relationship to "professional, " written history; whether games can (or need to) teach their players about the past; and the troublesome reoccurrence of and reliance on certain difficult terms, such as "historical accuracy" and "historical authenticity." This essay argues that all three of these fundamental aspects of our current approaches to historical game studies require further criticality to build on the foundational work of Playing with the Past as well as the vital work published in the field over the last decade.